Development of Marine Ecotourism in Indonesia: Case of Maligi Nature Reserve, Province of West Sumatra. Issue 1 (March 2021) - Zamzami, L.; Azwar,; Ermayanti,; Hendrawati,
Abstract: Arafura Sea is rich in its resources, e.g. shrimp, pelagic fish, demersal fish, and coral reef fish. Coral reef fish commonly found in Arafura waters are among others brown-marbled grouper, slender grouper, leopard coral grouper, humpback grouper, etc. One of the groupers that has a higher selling price than the other groupers is slender grouper ( Anyperodon leucogrammicus) . The high demand for the fish is in line with the increase in the catch and the exploitation status. Therefore, a study is necessary to analyze the exploitation status of the slender grouper in Arafura Sea. This study was carried out from March to November 2017 by sampling the grouper at its landing site in Dobo, Aru Islands, from the fishing grounds in Arafura Sea, Maluku. The size of the slender grouper was 15–120 cm TL, and its growth pattern was allometric negative. Its growth rate (K) was 0.34 per year and its fishing mortality (F) was higher than the natural mortality (M). The exploitation rate (E) of the fish was 0.52%, meaning the fish was already moderately exploited. Therefore, precautionary managements are necessary to maintain the sustainability of the slender grouper resources in Arafura Sea.